Clinical outcome of primary cemented hemiarthroplasty in unstable trochanteric fractues in elderly patients - Mukherjee, Jayanta; Ganguli, Ritwik (International Journal of Research in Orthopaedics, 2018)
Background: Management of unstable trochanteric fracture in elderly patients is challenging due to poor bone quality. Fracture stabilization and early mobilization is very important in preventing the complications. Fixation of the fracture with proximal femoral nail and dynamic hip screw has its complication and it takes time to mobilization of the patient after consolidation of fracture. Cemented bipolar hemiarthroplasty in osteoporotic unstable comminuted trochanteric fracture helps in early mobility and reduces complications. Methods: We prospectively analyzed 20 cases of cemented hemiarthroplasty in unstable intertrochanteric fractures. The functional outcomes were assessed based by Harris hip score. Results: The functional outcome measured with Harris hip score is excellent to good in most of the patients. Conclusions: Primary cemented hemiarthroplasty in unstable trochanteric fracture in elderly results in early ambulation with good functional outcome.